Bone fragments displacement in the treatment of diaphyseal fractures and their importance to the process of bone regeneration - Popsuishapka, Olexii; Litvishko, Valeriy; Ashukina, Nataliya; Іakovenko Svetlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Methods of fixation are used for the treatment of diaphyseal fractures, which produce structure «fragments – fixation device» with various mechanical properties and the displacement range of fragments. Purpose: to justify the concept of the effect of the displacement of bone fragments in the process of formation of the regenerate in the treatment of diaphyseal fractures with orthosis or external rod device (ARD). Methods: dislocation of the bone fragments using ultrasonography studied in 18 patients with diaphyseal fractures of humerus (9), femur (5) and tibia (5). Eight patients out of them with acute humeral fractures were treated conservatively with orthosis, in 5 patients with acute femoral and tibial fractures ARD was used, 6 patients had nonunion after osteosynthesis. Results:it is found that bone fragments have a multidirectional path of movement in space. In patients with acute humeral fractures treated with orthosis, linear displacement of the fragments end ranged 1.1–6 mm (10–40 % of initial distance), angular amplitude was 2°–8°. In ARD fixation linear fragment displacement (2 mm — 13 %) found only in patients with femoral fractures. In a cases of nonunion angular skeletal deformation appeared and increased under the axial load (apical deformity angel 13–40 %). The mobility of bone fragments in the first three weeks after diaphyseal fracture causes deformation and strain blastema, which results in the future structure of the high-grade periosteal bone regenerate. Nonunion of diaphyseal fracture fragments mobility does not provide a stimulating and shaping effect.